1988
DOI: 10.1002/jbt.2570030406
|View full text |Cite
|
Sign up to set email alerts
|

Toluene‐induced alterations in rat synaptosomal membrane composition and function

Abstract: Toluene is a widely used organic solvent that can produce acute central nervous system (CNS) effects. Since toluene reaches relatively high concentrations in the CNS and is extremely lipophilic, we investigated its effects on rat brain membrane composition and function. Toluene (1 g/kg, lh) did not alter total brain microsomal phospholipid (PL) or cholesterol (CL) content. However, synaptosomal PL was decreased (24%), while synaptosomal CL was unaltered. The PL/CL ratio, an indirect index of membrane fluidity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…All tissues examined showed an increase in ROS generation at the time of peak toluene blood levels (2 h after dosing). The blood toluene values reached in the current study, parallel those previously reported following a similar dosing regimen (LeBel and Schatz, 1988). This prior report also showed that brain levels of toluene are very similar to concurrent blood levels suggesting very rapid diffusion into the CNS.…”
Section: Discussionsupporting
confidence: 89%
“…All tissues examined showed an increase in ROS generation at the time of peak toluene blood levels (2 h after dosing). The blood toluene values reached in the current study, parallel those previously reported following a similar dosing regimen (LeBel and Schatz, 1988). This prior report also showed that brain levels of toluene are very similar to concurrent blood levels suggesting very rapid diffusion into the CNS.…”
Section: Discussionsupporting
confidence: 89%
“…The presently used low-dose toluene exposure did not affect membrane fluidity in the frontoparietal cortex, neostriatum, and subcortical limbic region, in agreement with the lack of effects following 500 ppm of toluene for 1 day up to 78 weeks [22) and of intraperitoneal injections (I g/kg) of toluene [46), but in contrast with the increase in membrane fluidity seen after toluene treatment in vitro (2.5 mmol/l, 10 mmol/I) [22,23). Thus, it seems as if changes in membrane fluidity [20,47) cannot fully explain the effects of toluene exposure in vivo on D-2 receptor binding even though the affinity of D-2 agonist binding sites are similarly reduced by in vivo and in vitro treatment [20,21), as is the modulation of D-2 agonist binding sites by neurotensin in vitro [21).…”
Section: Areasupporting
confidence: 76%
“…The rationale for the doses and time-course used was based on previous studies that demonstrated maximal 879 c. J. MATTIA, c. P. LEBEL ands. C. BONDY cerebral levels of toluene within the brain, concurrent with pronounced sedative effects under these conditions [8][9][10]. Metyrapone (200 mg/kg, i.p., 4 mL/kg) was also dissolved in corn oil and given 1 hr prior to toluene.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…From a mechanistic viewpoint, several recent studies have centered around the ability of toluene to alter neuronal membrane fluidity [8][9][10][11], levels of intracellular Ca 2 + and Ca 2 + -regulated events [11,12], and neuronal and astrocytic culture morphology [13]. Although it is unclear which of these events is causal to the neurotoxicity of toluene, these studies provide strong evidence to suggest that membraneassociated phenomena are integral to the mechanism of action of this solvent.…”
mentioning
confidence: 99%